Society of Maternal–Fetal Medicine Annual Meeting and a Continuing Medical Education Course: Results of Pre- and Postcourse Survey - Johnson, Julie M.; Chauhan, Suneet P.; Lopes, Vrishali; Sibai, Baha; Abuhamad, Alfred Z. (American Journal of Perinatology, 2012)
Objective To assess the influence of a continuing medical education (CME) course on knowledge acquired and potential to change clinical management or opinion.Study Design During the annual Society of Maternal–Fetal Medicine meeting, a survey consisting of 11 knowledge-based, 10 management plan, and 8 opinion questions was administered at the start and completion of the CME course. Chi-square and Fisher exact test were used, and p < 0.05 was considered significant.Results The survey was administered electronically to 394 attendees. Questions assessing knowledge showed significant improvement with 91% (10/11) of queries. Purported management changed significantly with 60% (6/10) scenarios and opinions in 62% (5/8) of clinical situations.Conclusion A survey done at the completion of a course indicates that CME improves knowledge and can change management and opinions. The prolonged benefits of CME need to be investigated.
Keywords: CME; pre-course; postcourse; MFM; survey